2022
DOI: 10.1021/acsomega.1c06523
|View full text |Cite
|
Sign up to set email alerts
|

Study on the Formation Characteristics of CO2 Hydrate and the Rheological Properties of Slurry in a Flow System Containing Surfactants

Abstract: Adding low dosage hydrate inhibitors to the hydrate systems makes the generated hydrate particles more uniformly dispersed in the liquid phase, which can significantly reduce the hydrate accumulation and blockage in oil and gas pipelines. The effect of surfactant hydrophile–lipophilic balance (HLB) values on hydrate flow characteristics was studied with a flow loop. The experimental results showed that there was a critical HLB value. When the HLB value was 4.3–9.2, it had an inhibitory effect on the hydrate in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 44 publications
0
10
0
Order By: Relevance
“…Studies have further shown that water-based nanofluid particles can enhance the number of hydrate nucleation sites and promote heterogeneous nucleation. 23,206 This increases the rate of hydrate nucleation and shortens the induction time for hydrate formation. 23 Furthermore, the addition of kinetic accelerators or promoters, as mentioned in various studies, has proven beneficial in improving the efficiency of hydrate formation by optimizing the crystallization process.…”
Section: Pressure Management Strategies Formentioning
confidence: 99%
“…Studies have further shown that water-based nanofluid particles can enhance the number of hydrate nucleation sites and promote heterogeneous nucleation. 23,206 This increases the rate of hydrate nucleation and shortens the induction time for hydrate formation. 23 Furthermore, the addition of kinetic accelerators or promoters, as mentioned in various studies, has proven beneficial in improving the efficiency of hydrate formation by optimizing the crystallization process.…”
Section: Pressure Management Strategies Formentioning
confidence: 99%
“…The hydrate formation, agglomeration, and deposition were observed experimentally in their works . Lv et al experimentally investigated the CO 2 hydrate formation and flow characteristics in the gas–oil–water flow system . The effect of the surfactant could make hydrate particles disperse in the liquid phase more uniformly .…”
Section: Introductionmentioning
confidence: 98%
“…However, for hydrate formation in a bubble column or bubble flow, the environment becomes a gas–liquid two-phase flow condition. Different from the hydrate formation on the single bubble, the hydrate shell would be broken by the effect of the high-speed flow during the hydrate formation, which makes formation characteristics much more complex. Luo et al used a single pipe with a stirrer to investigate the tetrahydrofuran hydrate formation in a bubble column in the static aqueous solution . Shimizu et al experimentally investigated the methane hydrate formation processes in the methane–water bubbly flow using a flow loop .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations